Evaluasi Simpang Bersinyal (Ber – Apill) Tanjung Barat – Pasar Minggu Berdasarkan MKJI dan Kondisi Lapangan - Hikma Dewita - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2015)
Signalized Intersection (air-APILL) Tanjung Barat – Pasar Minggu (South Jakarta) is an intersection that had existed before the overpass (fly over) TB. Simatupang was built. Currently the number of vehicles entering the intersection is moving slowly due to the density of traffic flow and as a result of delay (delay). In addition, the presence of lines KRL Jakarta - Depok - Bogar traffic with a frequency high pass makes congestion worse. The purpose of this the research was to evaluate performance of signalized intersection (air-APILL) Tanjung Barat – Pasar Minggu (South Jakarta) adjust arrangements the existing traffic ligtht with arrangement traffic ligtht from the result of the planning (MKJI).Primary data is obtained by performing a direct survey in the field. Data was processed and analyzed with reference MKJI up performance earned junction. Parameters which will be considered are cycle time, degree of saturation, the number of vehicles queued, long queues, delays and service level junction. It is advisable to avoid the traffic congestion of both traffic flow, the existing cycle time adjusted to the results of the planning cycle time.